2012
DOI: 10.1021/jp305220m
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Assignment of the Ultrafast Infrared Spectrum of the Photoactivatable Flavoprotein AppA

Abstract: The blue light using flavin (BLUF) domain proteins, such as the transcriptional antirepressor AppA, are a novel class of photosensors that bind flavin noncovalently in order to sense and respond to high-intensity blue (450 nm) light. Importantly, the noncovalently bound flavin chromophore is unable to undergo large-scale structural change upon light absorption, and thus there is significant interest in understanding how the BLUF protein matrix senses and responds to flavin photoexcitation. Light absorption is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 31 publications
4
60
1
Order By: Relevance
“…9,11,18 In addition, the bleach observed at 1670 cm –1 in lBlsA is absent in both dF32N and lF32N BlsA, while a strong bleach is observed at 1642(3) cm –1 in both dF32N BlsA and lF32N BlsA. The 1642(3) cm –1 band is similar to the frequency of the C2=O observed in AppA BLUF 11,12 and is unaffected by 13 C labeling of the protein, indicating that it is a flavin mode. Because isotopic editing of the flavin chromophore revealed that the 1670 cm –1 bleach in wild-type lBlsA is the C2=O carbonyl, the simplest explanation is that the Asn at position 32 in F32N BlsA H-bonds to the C2=O, resulting in a red shift in the frequency of this vibration.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…9,11,18 In addition, the bleach observed at 1670 cm –1 in lBlsA is absent in both dF32N and lF32N BlsA, while a strong bleach is observed at 1642(3) cm –1 in both dF32N BlsA and lF32N BlsA. The 1642(3) cm –1 band is similar to the frequency of the C2=O observed in AppA BLUF 11,12 and is unaffected by 13 C labeling of the protein, indicating that it is a flavin mode. Because isotopic editing of the flavin chromophore revealed that the 1670 cm –1 bleach in wild-type lBlsA is the C2=O carbonyl, the simplest explanation is that the Asn at position 32 in F32N BlsA H-bonds to the C2=O, resulting in a red shift in the frequency of this vibration.…”
supporting
confidence: 62%
“…9,10 Because BlsA is a photoactive BLUF protein and also has the conserved glutamine (Q51, Figure S3, Supporting Information), this transient mode must either be absent or obscured in dBlsA. Similar to AppA BLUF , 9,11,12 a bleach at 1700 cm –1 in dBlsA is shifted by 10 cm –1 to 1690 cm –1 in lBlsA and is assigned as the C4=O carbonyl of the flavin. A decrease in frequency is indicative of an increase of H-bonding to the flavin in the light-adapted state.…”
mentioning
confidence: 99%
“…The next two bleaches at lower wavenumber (1630, 1585 cm -1 ) are ring modes with significant C4aN5 stretch contributions, and the most intense bleach (1550 cm -1 ) is a C10aN1 dominated mode. 34-36 The three transient absorptions (1385, 1430, 1615 cm -1 ) in the 2 ps spectrum are due to vibrations of the FMN singlet excited state, 1 FMN*. Significantly, two additional bleaches are well resolved in the 2 ps spectrum of AsLOV2 (at 1690 and 1670 cm -1 ), which must arise from vibrational modes of amino acids interacting with the chromophore.…”
Section: Resultsmentioning
confidence: 96%
“…2A shows marked differences between TRIR spectra of aqueous FMN and AsLOV2, with the latter revealing much richer structure in the 1600 – 1750 cm -1 region. The vibrational spectrum of FMN itself has been assigned; 34-36 the bleaches at 1660 cm -1 and 1700 cm -1 (Fig. 2A) are associated with C=O vibrations of isoalloxazine, which comprise a coupled pair with the higher wavenumber mode more localized on C4=O and the lower on C2=O.…”
Section: Resultsmentioning
confidence: 99%
“…These data are compared with TRIR of AppA BLUF mutants and model flavins which unambiguously display the spectra of radical intermediates. 5557 In this way marker bands for neutral and radical states are identified. These assignments are confirmed by isotope substitution.…”
Section: Introductionmentioning
confidence: 99%